THE COMMAND ECONOMY IN THE DIGITAL AGE OF 2026: HOW AUTHORITARIAN STATES ADAPT TO AI AND GLOBAL SANCTIONS - Ignatius Septo Pramesworo; Hadenan Towpek (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This article analyses the evolution of the command economy system in the digital era of 2026, focusing on the adaptation of authoritarian states to artificial intelligence (AI) and global sanctions. Through a qualitative-descriptive approach based on library research, the study identifies how AI transforms traditional centralised planning into an adaptive model that utilises real-time data, algorithmic predictions, and digital sovereignty to overcome the limitations of classical information systems. Case studies of China (dual circulation, e-CNY) and Russia (alternative payment systems) demonstrate the application of AI in logistics optimisation, CBDCs for sanctions evasion, and microeconomic surveillance that strengthens resilience against Western pressure. Findings from this research reveal the paradox of techno-authoritarianism: whilst technically efficient, these models face risks of brain drain, fragmentation of global innovation, and cyber vulnerabilities that could undermine long-term sustainability. Geopolitically, AI-driven command economies contribute to a digital multi-polar world, eroding the effectiveness of traditional sanctions and challenging liberal economic hegemony. The article concludes that this adaptation is not merely a matter of survival, but an offensive strategy demanding a global response in the form of AI regulation and international technology governance dialogue to maintain a balance between economic efficiency and democratic values.